Early Childhood Caries, Masticatory Function, Child Early Cognitive, and Psychomotor Development: A Narrative Review - Bramantoro, Taufan; Mardiyantoro, Fredy; Irmalia, Wahyuning Ratih; Kristanti, Risma Aprinda; Nugraha, Alexander Patera; Noor, Tengku Eleena Binti Tengku Ahmad; Fauzi, Asra Al; Tedjosasongko, Udijanto (European Journal of Dentistry, 2023)
Dental caries is known as a global public health issue that has been affecting general health apart from its painful nature. Hence, it is undeniable that caries affecting young children or known as early childhood caries, also have an effect on children's general health. One of the interesting findings about caries is that it can also affect child growth and development, specifically on their cognitive and psychomotor ability. Untreated caries are linked to cognitive development through both neural and vascular pathways, with masticatory function as the key. Meanwhile, its effect on psychomotor development might be related to nutritional intake, which might slightly decline on those with caries. This review is aimed to describe the current findings of caries effect on early child development, from masticatory disturbance to further impacts on cognitive and psychomotor development. The overall conclusion of this review is that untreated severe caries in children are potentially associated negatively with their growth and development.
Keywords: caries; medicine; masticatory dysfunction; cognitive development; psychomotor development